War crimes with impunity: the case of Abu Ghraib prisoners - Eishan Jan, Mohammad Naqib (Serials Publications, 2006)
the graphic and real images of Iraqi prisoners being totured, murdered and sexually humiliated by United States (US) troops at the Abu Ghraib prison near Baghdad have shocked the conscious mind of civilized mankind and exposed to the world mot only the utter legal and moral bankruptcy of America's war on Iraq but also exposed American forces as to how sadistic, brutal and inhumane their conduct of armed conflict is. This paper attempts to determine the legalstatus of the detainees in Abu Gharaib prison, the type of crime they were subjected to, and the individual responsibility of the perpetrators of the crime. Who were the detainees in Abu Ghraib prison? Are they 'prisoners of war" or 'civilian detainees'? Do the torturous tratments they were subjected to come within thw definition of 'war crime'? If it is a war crime to torture the detainees then it is essential to determine the following questions: Who can be charged for such crimes? The oedinary solder or those who are in command and control, or both? Whose responsibility is it to try the alleged war criminals and, if found guilty, punish them? While discussing these questions the paper refers to the international humanitarian laws (IHL) as enshrined inter alia in the Geneva Conventions of 1949 (the most relevant of which is the Convention relative to the Protection of Civilian Persons in Time of War), relevant international human rights treaties, customary international law and decisions of international and national courts. An analysis of the relevant provisions of these laws reveal that the detainees were subjected to war crimes and the US has a primary responsibility to subject all the alleged war criminals, whether they are high ranking or ordinary military personals or civilian personals to a fair trial and if they are found guilty they must be punished-a punishment that must fit the crime.